Rice Washing Water as an Alternative to Liquid Organic Fertiliser (LOF) in Margamulya Village, Semangga District, Merauke Regency - Ineke Nursih Widyantari; Retnowati Wiranto; Stanly Hence Dolfi Loppies; Gerzon Jokomen Maulany (Universitas Muhammadiyah Palembang, 2024)
Semangga District is one of the rice-producing areas in Merauke Regency. One of the villages in Semangga District is Margamulya Village, which has 981 ha of agricultural land, 3,750 tonnes of rice production, and 5.4 tonnes/ha of rice productivity, a population of 2950 people, and 945 households. The population of Margamulya Village is occupied by farmers, with a total of 1069 people. This large population will produce large amounts of household waste as well, and if the waste is not processed, there will be a lot of garbage disposed of, which can damage the environment. Household waste will be more helpful if further processing is carried out, such as liquid organic fertilizer (LOF), which has many benefits for farmers. The main objectives of this community service are 1) to Help provide alternative organic fertilizer for farmers and 2) to help farmers get additional income. The method used in this service is to provide socialization and technical guidance on making liquid organic fertilizer (LOF) from household waste and packaging and marketing LOF. The technical guidance activities went well, and all village-level officials supported the service activities. With this activity, rice-washing water that was previously discarded becomes more practical and can be utilized as an alternative to increasing income in the family.